Korean female immigrants' lived experience with depression : a phenomenological study : a thesis presented in partial fulfillment of the requirements for a Masters of Philosophy in Psychology at Massey University - Lee, Simon Seung Wook (Massey University, 2002)
The aim of this study lies in describing and interpreting the meanings of Korean female immigrants' lived experience of depression. Depression is the most frequently occurring mental health diagnosis amongst immigrants. Waves of Korean immigrants have flocked to New Zealand for the last decade, and now the Korean language is the most common language after English in North Shore city. It is believed that a study on Korean female immigrants' mental health needs to be addressed by clinical professionals and mental health workers. Six Korean females who had lived for more than one year in New Zealand, and had once experienced depression were voluntarily selected and interviewed. The data was analysed by the following hermeneutic framework. The first chapter states the justification and impetus of the study, and the position of the researcher. It also contains an explanation about the focus and objectives of the study. The second chapter is dedicated to offering an opportunity to understand Korean culture in relation to the study's aim. The main social philosophy, religion, and norms are introduced to provide the reader with a better picture of Korean culture. The third chapter presents philosophical guidance for a hermeneutic study, and discusses how the framework has been applied to the study. The process of collecting and analyzing data and the ethical considerations that protect the participants' human rights and dignity are the main focus of this chapter. The findings section discusses four main themes which were classified to capture the core meaning of the participant's experiences. The last chapter discusses the limitations and recommendations that have emerged from the study. Notes Italics: The interview data from the study participants Names: Pseudonyms in Korean are used to protect the clients' anonymity. As English is not my first language, my proof readers, Emma and Leisa helped considerably to change my English into grammatically correct written English.
Keywords: Koreans; Women immigrants; Mental health; New Zealand; Depression in women